2014
DOI: 10.1185/03007995.2014.881794
|View full text |Cite
|
Sign up to set email alerts
|

Statins and asthma: where we stand, and the next critical steps in research

Abstract: Asthma remains a formidable public health problem with ever increasing annual costs and prevalence. There are 300 million people with asthma worldwide. Per the Centers for Disease Control and Prevention, there are over 25 million Americans with asthma (both children and adults), i.e. one in 12 people have asthma, and this is increasing annually. Asthma results in approximately half a million hospitalizations and two million emergency department (ED) visits per year. In 2007 alone, 185 children and 3262 adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Previous studies using rodent models of asthma and chronic obstructive pulmonary disease have demonstrated that systemic or airway administration of statin compounds (simvastatin, pravastatin or pitavastatin) alleviate airway inflammation, goblet cell hyperplasia/mucin production and initial signs of airway remodeling known to contribute to airway hyper-reactivity and smooth muscle hypertrophy/hyperplasia (Davis et al 2013;Zeki et al 2013Zeki et al , 2015Zeki, 2014;Bhattacharjee et al 2015;Wu et al 2017). Statin drugs specifically inhibit 3-hydroxy-3-methyl-glutaryl-CoA reductase, an enzyme that functions as the rate limiting step in the mevalonate pathway, which leads to cholesterol biosynthesis (Stancu & Sima, 2001;Cerqueira et al 2016).…”
Section: Statin Drugs and Allergic Airway Diseasementioning
confidence: 99%
“…Previous studies using rodent models of asthma and chronic obstructive pulmonary disease have demonstrated that systemic or airway administration of statin compounds (simvastatin, pravastatin or pitavastatin) alleviate airway inflammation, goblet cell hyperplasia/mucin production and initial signs of airway remodeling known to contribute to airway hyper-reactivity and smooth muscle hypertrophy/hyperplasia (Davis et al 2013;Zeki et al 2013Zeki et al , 2015Zeki, 2014;Bhattacharjee et al 2015;Wu et al 2017). Statin drugs specifically inhibit 3-hydroxy-3-methyl-glutaryl-CoA reductase, an enzyme that functions as the rate limiting step in the mevalonate pathway, which leads to cholesterol biosynthesis (Stancu & Sima, 2001;Cerqueira et al 2016).…”
Section: Statin Drugs and Allergic Airway Diseasementioning
confidence: 99%
“…The effectiveness of statins in asthma is biologically plausible and the inhibition of the MA pathway by statins offers a unique treatment opportunity in severe asthmatics, as this pathway is not affected by corticosteroids, β-agonist therapies, or any other current therapies [8789]. …”
Section: The Mevalonate Pathway Statins and Relevance To Asthmamentioning
confidence: 99%
“…peak expiratory flow rate, forced expiratory volume in the first second (FEV1), forced vital capacity (FVC)), airway inflammation (sputum cell counts and cytokine levels), symptom surveys, and quality-of-life score(s) [53,55–60,87]. However, results from these RCTs have produced equivocal and at times conflicting results.…”
Section: The Mevalonate Pathway Statins and Relevance To Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…This in turn might be responsible for variations in the actions of statins against various diseases. Additionally, the question arises as to whether the mucosal epithelial immunity and alveolar capillary barriers in the respiratory compartment interfere with the action of statins [ 121 ].…”
Section: Clinical Trialsmentioning
confidence: 99%